2021
DOI: 10.1080/13543784.2021.1897786
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in phase I and II clinical development for the prevention of stroke in patients with atrial fibrillation

Abstract: Introduction: Atrial fibrillation is the most frequently diagnosed cardiac arrhythmia globally and is associated with ischemic stroke and heart failure. Patients with atrial fibrillation are typically prescribed long-term anticoagulants in the form of either vitamin K antagonists or non-vitamin K antagonist oral anticoagulants; however, both carry a potential risk of adverse bleeding. Areas Covered: This paper sheds light on emerging anticoagulant agents which target clotting factors XI and XII, or their activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…53 Expanding partnerships with health systems to conduct RCTs that evaluate system-level interventions to improve the use of OACs in AF patients considered at high stroke risk (eg, IMPACT-Afib 54 New OACs that further lower bleeding risk (particularly intracranial hemorrhage) while preserving efficacy are needed, including evaluation of Factor XIa and Factor XIIa inhibitors. 39 Whether patients with lower AF burden should use as needed DOAC dosing is unknown, 55 and RCTs such as the proposed REACT COM trial (Rhythm Evaluation for Anticoagulation With Continuous Monitoring) of rhythm-guided anticoagulation paired with smartwatch and daily ECG monitoring, 56 among others, may provide additional clarity. These and other advances may promote customized OAC use and dosing to maximize the long-term medication adherence and stroke prevention at the lowest absolute bleeding risk.…”
Section: Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Expanding partnerships with health systems to conduct RCTs that evaluate system-level interventions to improve the use of OACs in AF patients considered at high stroke risk (eg, IMPACT-Afib 54 New OACs that further lower bleeding risk (particularly intracranial hemorrhage) while preserving efficacy are needed, including evaluation of Factor XIa and Factor XIIa inhibitors. 39 Whether patients with lower AF burden should use as needed DOAC dosing is unknown, 55 and RCTs such as the proposed REACT COM trial (Rhythm Evaluation for Anticoagulation With Continuous Monitoring) of rhythm-guided anticoagulation paired with smartwatch and daily ECG monitoring, 56 among others, may provide additional clarity. These and other advances may promote customized OAC use and dosing to maximize the long-term medication adherence and stroke prevention at the lowest absolute bleeding risk.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…38 Yet, achieving optimal net benefit from available OACs remains elusive, and evaluation is needed for additional OACs that may be safer without sacrificing stroke prevention efficacy. 39…”
Section: Introductionmentioning
confidence: 99%
“…33 A phase II clinical trial (NCT04213807) has been performed to adjust a dose of abelacimab in AF patients in whom anticoagulation is not indicated. 29 However, it is unknown whether FXIa inhibition could be useful in stroke prevention in AF and our study might provide the rationale to test this hypothesis.…”
Section: Discussionmentioning
confidence: 90%
“…Several new approaches have been developed to attenuate FXI or FXIa, including inhibition by the natural form of TF pathway inhibitor, specific antibodies or fusion proteins that block FXI activation, antisense oligonucleotides, DNA aptamers, and others. [29][30][31] A recent trial showed that abelacimab, a monoclonal antibody that binds to FXI and inhibits its conversion to the active form, reduced VTE risk to a greater extent than enoxaparin in patients after knee arthroplasty and was associated with a low bleeding risk. 32 A monoclonal antibody inhibiting FXIa (osocimab) administered preoperatively was superior to enoxaparin in VTE prevention.…”
Section: Discussionmentioning
confidence: 99%